Conselhos de Administração, Board Interlocking e Análise de Redes das empresas listadas no Nível 2 de Governança Corporativa da B3 - Oliveira, Jéssica Maria de (2022)
This dissertation aims at exploring the intrinsic characteristics of the Board of Directors, verifying the conformity of such boards with the stablished good practices of Corporate Governance while also exploring the Board Interlocking that exists in said boards with the help of Network Analysis. It also aims to map the shareholder composition of the studied companies composed by a sample of Level 2 of Corporate Governance of B3 from the year 2017. For that, we used a theory-based research in which he data collection in order to reach the objectives was achieved through a bibliographic and documental research. In order to analyze the networks of the Board Interlocking, we used the Gephi software to draw the networks of interest and make the measurements of Modularity, Intermediation Centrality, Degree Centrality and Proximity Centrality. The results regarding the characteristics of the Board of Directors shows board members with notable professional careers and academic legitimacy, little feminine participation and boards composed mostly by family members. The results regarding the conformity of the Board of Directors with the good practices of Corporate Governance show that the size of the boards to be in accord to the legislation, CEOs/Vice-CEOs holding also the positions of Chariman/Vice-Chairman and once more the issue of family members with control of the board composition. Last, the results for Board Interlocking, one research showed that 80,9% of the board members of the analyzed companies were interlocked, meaning that they participated in ate least two different boards, connecting the sample to other 789 organizations. Of the 20 companies, only 2 (AES Tietê and AES Eletropaulo) connected directly through the Board Interlocking. Another analysis assessed the inter-board Board Interlocking in which 14 of the 20 assessed companies had two or more board members acting together in another 46 companies not listed At the Level 2 of the Corporate Governance of the B3. A third analysis showed that a subset of 42 companies not listed at the Level 2 of Corporate Governance of B3 (from the total of 789) which connect 18 companies listed at Level 2 of Corporate Governance (of the 20), with the exception of Celesc e and Gol. A network analysis was made using Gelphi, identifying 5 clusters; AES Eletropaulo, AES Tietê, Marcopolo and Renova had a higher degree centrality and intermediation; ABDIB, IBGC, AMEC, AES Tietê and AES Eletropaulo had higher proximity indicator. We also gathered data for the shareholder position of the 20 companies, in which 7 of them share investors. This network was drawn in tandem with the third analysis to verify which factors could complement the corporate relations. The Board Interlocking proved to be, therefore, a primordial factor to the network analysis, specially by the fact that the Board of Directors has several members that provide a myriad of connections. For future works, taking the shareholders position, underlying questions could also be analyzed in order to make clarify the corporate ties and the complexity of the networks made by them.